Dialectics of Religious Conversion of Air Sanih Community in Singaraja - Raka, I Nyoman; Gunawijaya, I Wayan Titra (Jayapangus Press, 2023)
Air Sanih community underwent changes after being developed into a tourism destination. The sacred pool (pertirtan), converted into a paid tourist attraction. Changing the sacred pool into a paid pool is done for material gain. The emergence of GoMas (Goa Maria Air Sanih) has had an impact on religious practices. A number of members of the Air Sanih community turned away, making the Virgin Mary their god of worship. This study aims to determine the dialectic, deviation, and religious conversion of the Air Sanih community, through qualitative methods through primary and secondary data sources, namely information from the Air Sanih community and supporting literature data through a phenomenological approach. The results of the study explain dialectics as the impact of developing a village into a tourism destination. The entry of tourism provides new understanding and experience to the people of Air Sanih. A new understanding in the field of religious patterns has made people turn to certain religious patterns, namely making the Blessed Virgin Mary a Ista Dewata (eight existence of God), a deity to worship. This is done by a number of Hindus who have a tradition of using a prayer facility in the form of a daksina linggih (Balinese offering which function as a God’s chair/seat) in front of the statue of the Virgin Mary. Indirectly making the Virgin Mary a worshiped God, without leaving Ida Sang Hyang Widhi as the initial worshiping God, is an internal religious conversion.